2022
DOI: 10.3389/fcvm.2022.824756
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Communal Pathogenesis, Ferroptosis Mechanism, and Potential Therapeutic Targets of Dilated Cardiomyopathy and Hypertrophic Cardiomyopathy via a Microarray Data Analysis

Abstract: BackgroundCardiomyopathies are a heterogeneous group of heart diseases that can gradually cause severe heart failure. In particular, dilated cardiomyopathy (DCM) and hypertrophic cardiomyopathy (HCM) are the two main types of cardiomyopathies, yet the independent and communal biological mechanisms of both remain far from elucidated. Meanwhile, ferroptosis is a non-apoptotic form of cell death that has been proven to be associated with cardiomyopathies, but the concrete nature of the interaction remains unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…Another annotation term that was up-regulated in LVRR- vs LVRR+ patients was the cell adhesion. Cell adhesion pathways have been found to be dysregulated on the transcriptome level in the DCM heart tissue. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another annotation term that was up-regulated in LVRR- vs LVRR+ patients was the cell adhesion. Cell adhesion pathways have been found to be dysregulated on the transcriptome level in the DCM heart tissue. , …”
Section: Discussionmentioning
confidence: 99%
“…Cell adhesion pathways have been found to be dysregulated on the transcriptome level in the DCM heart tissue. 51,52 The most prominent among the proteins up-regulated in the nonresponding LVRR− patients was fructose-bisphosphate aldolase B (ALDOB). In a study by Rueda et al 53 ALDOB was used as one of four proteins to predict the low-term risk of mortality in patients with cardiogenic shock.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The leading cause of Friedreich's ataxia-related death is HCM, which is attenuated by the combined therapy of idebenone and oral low-dose deferiprone [64,65]. Microarray data analysis showed that some ferroptosis genes are associated with HCM, such as ATF3, LPCAT3, and solute carrier family 1 member 5 (SLC1A5) [66]. Diabetic Cardiomyopathy DCM is a pathophysiological condition caused by diabetes that contributes to HF where the decline of myocardial cell function is an important mediating mechanism [67].…”
Section: Iron Overload Cardiomyopathymentioning
confidence: 99%
“…The leading cause of Friedreich’s ataxia-related death is HCM, which is attenuated by the combined therapy of idebenone and oral low-dose deferiprone [64, 65]. Microarray data analysis showed that some ferroptosis genes are associated with HCM, such as ATF3, LPCAT3, and solute carrier family 1 member 5 (SLC1A5) [66].…”
Section: Ferroptosis and Cvdmentioning
confidence: 99%
“…Second, STAT3 is the direct target of miRNA. Some miRNA predicted to target STAT3, which is an inhibitor of ferroptosis in DCM ( 37 ). In summary, STAT3-miRNA protects the heart against DCM.…”
Section: Stat3-mirna Crosstalk In Dilated Cardiomyopathymentioning
confidence: 99%